Opening eyes onto inclusion and diversity - Carter, Susan; University of Southern Queensland; BC Open Textbook Project; BCcampus (University of Southern Queensland, 2019)
"In Australia and internationally much still needs to occur to promote inclusive practices in education and society with many educators not feeling equipped to recognise or appreciate diversity or cater effectively for inclusion. With embedded audio-visual components, this open textbook is designed to enhance the quality of the reader's experience with each chapter posing key understandings underpinning inclusion and diversity. Readers are encouraged to answer questions on culture, special learning needs, varied educational contexts, gender diversity and more. The key expected outcome of this open textbook is to engage readers in making meaning of inclusion and diversity and applying their learning to their own individual contexts."--BCcampus website.
This work is licensed under the Creative Commons Attribution-NonCommercial CC-BY-NC.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Includes bibliographical references.
Description based on online resource; title from pdf title page (viewed on October 18, 2019).
Keywords: Inclusive education -- Australia; Educational equalization -- Australia; Early childhood education -- Australia; Multicultural education -- Australia; Electronic books